Dorn's still for the distillation of alcohol (Encyclopædia of Chemistry, Theoretical, Practical, and Analytical, as Applied to the Arts and Manufacturers, Vol. I and II, 1877)
Still by Johann Friedrich Dorn used for the small scale distillation of fermented extract of malt.
Keywords: Distillation apparatus; Dorn, Johann Friedrich 1782-1835; Chemistry, Technical